2015
DOI: 10.1249/mss.0000000000000377
|View full text |Cite
|
Sign up to set email alerts
|

The Yo-Yo IE2 Test

Abstract: The Yo-Yo IE2 test was shown to possess high construct validity by showing large differences in performance, HR, and anaerobic metabolism between UTR and TR. In addition, V˙O2max seemed to be important for intermittent exercise performance in UTR but not for TR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 38 publications
4
15
2
Order By: Relevance
“…In our study, blood lactate concentrations are in line with the literature for YoYoIE2 ( Krustrup et al, 2015 ) in similar subjects (i.e., untrained) confirming also the significant anaerobic contribution to ATP supply. Another study showed that IPC generated lower blood lactate concentration at submaximal intensity during an incremental running test ( Bailey et al, 2012 ), but in the current study we did not find any difference among IPC, SHAM and control conditions.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, blood lactate concentrations are in line with the literature for YoYoIE2 ( Krustrup et al, 2015 ) in similar subjects (i.e., untrained) confirming also the significant anaerobic contribution to ATP supply. Another study showed that IPC generated lower blood lactate concentration at submaximal intensity during an incremental running test ( Bailey et al, 2012 ), but in the current study we did not find any difference among IPC, SHAM and control conditions.…”
Section: Discussionsupporting
confidence: 91%
“…; trivial effect sizes) of acute IPC on this sort of test and population. The distance covered in the current study in the control conditions (935 ± 232 m) is higher than that reported for untrained men (665 ± 271 m) but lower than highly trained soccer players (2,027 ± 298 m) ( Krustrup et al, 2015 ). Since the scores of perception of recovery were similar before all of the three trials (i.e., players starting under same conditions), basic conditions for comparison of different protocols were ensured.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Computation of YYIE2 test global means, SDs and quantiles (Figure 4) included 48 studies/subgroups and 1,466 participants (median age = 23.0 years, IQR = 18.3–26.0 years) (Aziz et al, 2005; Rampinini et al, 2007; Bangsbo et al, 2010; Brito et al, 2010; Krustrup et al, 2010a,b,c, 2015; Randers et al, 2010, 2013; Ascensão et al, 2011; Bradley et al, 2011, 2013, 2014; Rebelo et al, 2011, 2013; Silva et al, 2011, 2013; Gibson et al, 2013; Dixon, 2014; Massuça et al, 2014; Massuca et al, 2015; Matta et al, 2014; Póvoas et al, 2014; Kvorning et al, 2017). …”
Section: Resultsmentioning
confidence: 99%